The relationship between religiosity and physical and mental health in the optimal style of student life from the point of view of Quran and Hadith - Abbas Ahmadi,; Moghadam, Mostafa Abbasi; Fahimi Tabar, Hamid Reza (International Journal of Psychosocial Rehabilitation, 2020)
Based on human scientific and practical experience, physical and mental health is a prerequisite for success in life and lubrication is the path to the goal of life. The existence of micro and macro laws in economics, personal and social health, and political and social interactions in Islam shows that; Islam pays attention to lifestyle, although the rules and regulations are general but it should not be overlooked that the lifestyles of different classes vary according to the role they play in society. Therefore, students have been the target of many special laws because they are studying in a special place in the future of society. The question is what is the view of Islam on mental and physical health? What are the physical and mental health characteristics of the student from the Islamic point of view? What harms can be done to the Islamic student's lifestyle if there is no mental, psychological and physical health? What does religiosity have to do with physical and mental health? What is the role of the desirable lifestyle of the Qur'an and Hadith in the physical and mental health of the student? This article aims to examine and prove the "relationship between religiosity and physical and mental health, in the optimal style of student life from the perspective of the Qur'an and Hadith." The achievement is that religiosity and religion bring peace of mind to human beings. The Holy Quran has guidelines for the treatment of mental illnesses and their role in the student's lifestyle, as follows: 1- Physical health Introduction Mental health: Human physical and mental health has a two-way relationship, credit to physical health leads to mental health and mental health leads to physical health. There are instructions on observing the health of the body from the perspective of the Qur'an and hadith, such as: A- Observance of hygiene B- Eating less C- Correct consumption D- Sports. Each can be effective in maintaining mental health. 2- Mentioning and remembering God 3- Piety and avoidance of sin 4- Faith and purposefulness 5- Reading the Quran and praying 6- Ordering trust and hope for the future 7- Avoid contaminated food.